Intestinal obstruction caused by endometriosis: Endoscopic stenting and expedited laparoscopic resection avoiding stoma. A case report and review of the literature. (2018) - Calcagno, Pietro; Viti, Matteo; Cornelli, Alessandro; Galli, Davide; D'Urbano, Corrado
Highlights: Bowel obstruction due to deep infiltrating endometriosis is a rare event. Our case can be an example of a diagnostic process performed before surgical treatment. We show the feasibility of an expedited one step laparoscopic resection. Our approach has a lot of advantages for a young fertile woman with a chronic disease. Abstract: Introduction: Endometriosis is the growth of endometrium outside the uterine cavity. In 5–15% of cases the disease can affect the colon and small bowel, causing complete obstruction and requiring resection in about 1% of cases. Case summary: We describe a case of sigmoid obstruction due to endometriosis in a 38 years old woman with personal history of endometriosis. She was admitted for abdominal pain and constipation. The patient was treated with endoscopic stenting and subsequent laparoscopic sigmoidectomy. Discussion: Bowel obstruction caused by endometriosis is a rare event. Its diagnosis can thus be a clinical and radiological challenge but it may be suspected in all young woman with colonic obstruction. At present, the management of endometriosis is an integrate approach of both medical and surgical therapy. In case of irreversible colonic obstruction surgery is mandatory. The treatment of choice is usually an emergency procedure (either Hartmann procedure or resection and anastomosis with stoma placement). This approach entails all the risks related to emergency procedures and can have important psychological and biological drawbacks. Conclusion: Endoscopic prosthesis placement as bridge to surgery is a feasible therapeutic strategy in colonic obstruction due to endometriosis. It brings about all the advantages of an expedited one step laparoscopic surgical procedure. Laparoscopic elective resection has a lower rate of stoma placement and has a postoperative pregnancy rate grater than open surgery.